FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR SEKTOR KONSUMEN NON-PRIMER - Marcella Marcella; Augustpaosa Nariman (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aimed to find out how the influence of profitability, leverage, firm size, liquidity and cash flow on cash holdingin manufacturing companies consumer non-cylicals sector were listed on Indonesia Stock Exchange during the 2019-2021 period. The sample selection method in this study used a purposive sampling method with valid data of 48companies. The data were processed using multiple regression analysis techniques with the help of SPSS (Statistical Program for Social Science) Version 26 program and Microsoft Excel 2010. The results of this study indicated that profitability and liquidity had significant positive effect on cash holding. The implication of this research is the need to increase profitability and liquidity in order to increase cash holding within the company.